The Essence of Isra'iliyyat Story in Tafsir Al-Qur'an - Zaelani, Agung Ahmad (UIN Sunan Gunung Djati Bandung, 2024)
This research was conducted departing from the dynamics of the problem in terms of various aspects and values regarding isra'iliyyat infiltration in interpretation. There are so many views that tend to be negative about it. Even there is another side, considering that it is a necessity of acculturation in socio-cultural life. This study used the library research method by collecting, processing, and inducing data in accordance with the discussion from various sources of literature, namely descriptive analysis. The purpose of this study is to mediate views regarding scientific substance in isra'iliyyat and the correlation of its infiltration into the interpretation of the Qur'an, which has been going on for a long time. So with this, it can be found values that correspond from the isra'iliyyat aspect with the basic values in the interpretation of the Qur'an. It is also hoped that this will stimulate the birth of a more intense study to trace isra'iliyyat genealogy whose purity is still maintained; of course, it does not mean to rule out the study of texts, namely the Al-Qur'an and al-Hadith. Seeing the material in its historical reality, isra'iliyyat and interpretation cannot be completely separated. This is because it has become a general reality that every culture will experience acculturation assimilation. Especially when this isra'iliyyat is interpreted etymologically as whatever is contained in the holy book of the people of the book from all its aspects.